THE RELATIONSHIP BETWEEN NURSING HUMAN RESOURCES AND THE IMPLEMENTATION OF PROLANIS WITH PARTICIPANT ENGAGEMENT IN COMMUNITY HEALTH CENTERS - Juliana Sabilla; Herman Ariadi; Sukarlan Sukarlan; Yustan Azidin (Jurnal Keperawatan Sriwijaya, 2026)
Aim: The Chronic Disease Management Program (Prolanis) is a strategic initiative of BPJS Kesehatan aimed at improving the quality of life of patients with chronic diseases through integrated services at primary healthcare facilities. The success of this program is influenced by the availability of nursing human resources, the implementation of program activities, and participant involvement. This study aimed to analyze the relationship between the availability of nursing human resources and the implementation of activities with the participation of Prolanis participants in Public Health Centers (Puskesmas) in Banjarmasin City. Method: This study employed a quantitative analytical observational design with a cross-sectional approach. The population consisted of 27 Public Health Centers in Banjarmasin City implementing the Prolanis program, with total sampling used as the sampling technique. Data were collected using observation checklists and documentation. Data analysis was conducted through univariate and bivariate analyses using Fisher’s Exact Test with a significance level of α = 0.05. Result: The results showed that most Public Health Centers had adequate nursing human resources (88.9%), and the implementation of Prolanis activities was categorized as achieved (85.2%). However, participant involvement in the Prolanis program was predominantly inactive (66.7%). Bivariate analysis indicated no significant relationship between the availability of nursing human resources and participant involvement (p = 0.529), nor between the implementation of activities and participant involvement in the Prolanis program (p = 0.268). Conclusion: The findings suggest that participant involvement in the Prolanis program is not solely influenced by the availability of nursing human resources and the implementation of activities, but also by other factors such as motivation, perceived benefits, and family and environmental support.